2018
DOI: 10.1002/agr.21548
|View full text |Cite
|
Sign up to set email alerts
|

Producer and farm characteristics, type of product, location: Determinants of on‐farm and off‐farm direct sales by farmers

Abstract: Direct sales are a widespread and important typology of the socalled alternative food networks. They can take two basic forms: consumers going to buy agricultural products at the farm (on-farm sales) and farmers selling their products in urban areas. We investigate the territorial distribution of direct sales practices (on-farm and off-farm) in Piedmont (Italy) and we assess the main determinants of these choices via probit models, separately for on-farm and off-farm sales. The explanatory variables comprise s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
4
15
2
Order By: Relevance
“…This result reveals that direct marketing options are more appropriate for semi-specialized farms. This result supports findings by Aguglia et al (2009), Detre et al (2011), Park et al (2011), and Corsi et al (2014), who concluded that as farms had become more specialized, they had a lower likelihood to market through DTC outlets. This result is also consistent with the findings of Park et al (2014) who concluded that farmers engaged in direct sales only tend to market a greater diversity of crops and have a larger variation in the earnings shares of those crops compared with farmers with no direct sales.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This result reveals that direct marketing options are more appropriate for semi-specialized farms. This result supports findings by Aguglia et al (2009), Detre et al (2011), Park et al (2011), and Corsi et al (2014), who concluded that as farms had become more specialized, they had a lower likelihood to market through DTC outlets. This result is also consistent with the findings of Park et al (2014) who concluded that farmers engaged in direct sales only tend to market a greater diversity of crops and have a larger variation in the earnings shares of those crops compared with farmers with no direct sales.…”
Section: Resultssupporting
confidence: 89%
“…The fully-specialized farms which had low crop diversity did not generally want to take risk to sell directly to consumers due to lack of knowledge and experience. As seen from the literature review, this hypothesis was also supported by the findings of Aguglia et al (2009), Detre et al (2011), Park et al (2011, 2014), and Corsi et al (2014) who concluded that as farms had become more specialized, they had a lower likelihood to market through DTC outlets.…”
Section: Methodssupporting
confidence: 62%
See 2 more Smart Citations
“…This grants customers access to fresher and heathier agri-foods [11,12]. In addition, consumers can enjoy the PYO experience [2,3,11,12,13], and the picking experience is also a selling point. Finally, PYO operations are also economically profitable for farmers.…”
Section: Introductionmentioning
confidence: 99%